Ratio-Legal Fazlur Rahman's Hermeneutics and Its Influence on Sisters-In-Islam - Latifah Abdul Majid; Sharifah Nayan (Jurnal Living Hadis, 2021)
Scholars of exegesis (interpretation) are unanimous on the method of interpreting al-Quran and Sunnah. However, Fazlur Rahman proposed a modern method of interpretation by applying hermeneutics. He held that this method is to obtain the universal moral values. His assumption is based on the need for al-Quran to be interpreted in a socio-historical context in order to obtain the reasons and purpose of the revealed text and its moral objectives. Fazlur Rahman’s method of interpretation and analysis has its influence on the Sisters-in-Islam (SIS) group.  The objective of this article is to evaluate Fazlur Rahman’s method of interpretation and analyse the influences of Fazlur Rahman’s method determine on women’s issues by the SIS group. This is a qualitative research which uses content analysis approach. Research results demonstrated that SIS have adopted Fazlur Rahman’s hermeneutics in expressing their ideas.